2020
DOI: 10.1101/2020.07.30.228882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optically pumped magnetometers disclose magnetic field components of the muscular action potential

Abstract: Aim: To track the magnetic field generated by the propagating muscle action potential (MAP). Method: In this prospective, proof of principle study, the magnetic activity of the intrinsic foot muscle after electric stimulation of the tibial nerve was measured using optically pumped magnetometers (OPMs). A classical biophysical electric dipole model of the propagating MAP was implemented to model the source of the data. Results: The signal profile generated by the activity of the intrinsic foot muscles was measu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…As experimentally measured by Broser et al. ( 2021 ), the proposed model predicts a triphasic shape of the overall magnetic muscle action potential caused by volume currents in the extracellular space. However, as volume currents strongly depend on the exact muscle geometry, a direct comparison to the experiments of Broser et al.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As experimentally measured by Broser et al. ( 2021 ), the proposed model predicts a triphasic shape of the overall magnetic muscle action potential caused by volume currents in the extracellular space. However, as volume currents strongly depend on the exact muscle geometry, a direct comparison to the experiments of Broser et al.…”
Section: Discussionsupporting
confidence: 60%
“…For example, Broser et al. ( 2021 ) used a finite wire model to infer from their measurements the underling physiology. However, this approach could not explain some of their experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…QuSpin OPM sensors are conformal with a 6.5 mm sensor stand-off that in aggregate contribute to an improved magnetic signal-to-noise ratio therefore capable of surpassing current SQUID sensor technology due to closer proximity to the neuronal source (Iivanainen et al, 2017;Hill et al, 2020). Recently Broser et.al., (Broser et al, 2018;Broser et al, 2020) showed that commercial Gen-1 OPMs (QuSpin Inc, CO, USA) detect compound muscle action currents consistent with motor neuron activation. Expounding on this work, we employed the commercially available Gen-2 OPM (QuSpin Inc, CO, USA) with the aim to measure upper extremity action currents equivalent to the SNAP and H-Reflex.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
“…This yields high technical demands for MMG recording systems (Zuo et al, 2020), for example, with respect to the sensitivity, the detection range, the sampling rate, the shielding from magnetic noise, the size and portability of the sensor device as well as the cost of such recordings. Nevertheless, a few proof-of-concept studies, e. g. Broser et al (2018Broser et al ( , 2021, Llinás et al (2020), Reincke (1993), illustrate its feasibility for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Common to all MMG models is that they first calculate the current field, which is then used to obtain the magnetic field. For example, Broser et al (2021) used a finite wire model to infer from their measurements the underling physi-ology. However, this approach could not explain some of their experimental observations.…”
Section: Introductionmentioning
confidence: 99%